2010
DOI: 10.1002/chem.201000296
|View full text |Cite
|
Sign up to set email alerts
|

Methane Activation by Platinum: Critical Role of Edge and Corner Sites of Metal Nanoparticles

Abstract: Complete dehydrogenation of methane is studied on model Pt catalysts by means of state-of-the-art DFT methods and by a combination of supersonic molecular beams with high-resolution photoelectron spectroscopy. The DFT results predict that intermediate species like CH(3) and CH(2) are specially stabilized at sites located at particles edges and corners by an amount of 50-80 kJ mol(-1). This stabilization is caused by an enhanced activity of low-coordinated sites accompanied by their special flexibility to accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
107
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 79 publications
(126 reference statements)
15
107
0
1
Order By: Relevance
“…Viñes et al [90] reported a TS energy of 1.06 eV for the RPBE functional and a computational setup similar to the one that we have used. Here, we have also obtained a larger E b value for the RPBE functional (about 1.17 eV, see Table 3).…”
Section: The Dissociation Barriermentioning
confidence: 92%
See 1 more Smart Citation
“…Viñes et al [90] reported a TS energy of 1.06 eV for the RPBE functional and a computational setup similar to the one that we have used. Here, we have also obtained a larger E b value for the RPBE functional (about 1.17 eV, see Table 3).…”
Section: The Dissociation Barriermentioning
confidence: 92%
“…[90] would include surface relaxation effects, which is not explicitly mentioned. In fact, the upward motion of the surface atom below the dissociating molecule has been shown to be able to lower the barrier by up to 0.15 eV for this system [49].…”
Section: The Dissociation Barriermentioning
confidence: 99%
“…Consequently, we assign the first step at ∼350 K to dealkylation at highly reactive low-coordinated defect sites on the metal particles. Previous studies on the dehydrogenation of ethylene 28 and methane 29 show that these low-coordinated sites are responsible for a substantial decrease of the activation barrier of dehydrogenation, as compared to Pt(111). The literature states that hydrocarbon activation is promoted by the presence of defect sites due to a stronger binding of the adsorbates.…”
Section: Adsorption and Thermal Evolution On Supported Pt Particlesmentioning
confidence: 93%
“…The literature states that hydrocarbon activation is promoted by the presence of defect sites due to a stronger binding of the adsorbates. 29 As a consequence, the kinetics and thermodynamics of dehydrogenation and degradation are strongly affected. We suggest that these findings can be transferred to the present system, which is reflected by a lowered temperature threshold of H x -NBC dealkylation on the supported Pt catalyst.…”
Section: Adsorption and Thermal Evolution On Supported Pt Particlesmentioning
confidence: 99%
“…Moreover, natural gas is an attractive alternative fossil fuel which could reduce pollutant emissions and lower the energy dependence on fossil oil [14,15,22]. However, methane is considered the most stable hydrocarbon and is difficult oxidize, and its catalytic ignition requires relatively high temperatures even on expensive Pt-or Pd-based catalysts [23][24][25][26][27]. Therefore, preheating the inlet mixture gases [28], adding hydrogen to the methane fuel [29,30] and improved catalyst layout designs [31,32] have been proposed in succession to improve the combustion efficiency in micro-reactors.…”
Section: Introductionmentioning
confidence: 99%